Being as the Unity of Substance and Accident in the Metaphysics of the Peripatetic - Zamirbek, Alymkulov; Tolobek, Abdyrakhmanov; Kayyrkul, Arypbekova; Askarbek, Bekboev; Duyshobek, Dzhanuzakov (Journal of Ecohumanism, 2025)
Representatives of “Falsafa” rationalistically interpreted the ontological and logical-epistemological nature of the categories. They tried to highlight the most general concepts about the world and ways of knowing it. Objective reality appears to Peripatetic thinkers, primarily as the unity of substance and accident. Therefore, the categorical table of the Eastern Peripatetics was built according to a certain system and, to a certain extent, corresponds to the principle of substantial connection of categories. The basis of the substrate of categorical statements is substance. Separate categories such as quality, quantity, relation, place, time, action, possession and others concretize from various sides and reveal its content and essence. Representatives of medieval Arabian philosophy on the basis of the teachings of ancient philosophers proposed number of philosophical concepts in their treatises. The separate categories put forward by Peripatetics as time, space, place, quality, quantity are revealed in their essential characteristics.